Ministerial Decree No. 432/2014 concerning list (44) for engineering products and goods / translated by The middle east library for economic services. - The middle east library for economic services, translator. (2025)
Ministry of Industry, Trade and Investment decree no. 432 of the year 2014 وزارة التجارة والصناعة والاستثمار قرار رقم 432 لسنة 2014